ma poate ajuta cineva?
![Ma Poate Ajuta Cineva class=](https://ro-static.z-dn.net/files/dd8/d52d0e3455a03847d17ef61e1b9e9437.jpg)
Explicație pas cu pas:
[tex]a)a \times {a}^{2} = \\ \\ {a}^{1} \times {a}^{2} = \\ \\ {a}^{1 + 2} = \\ \\ {a}^{3} [/tex]
[tex]c)( - 4x) \times 3y = \\ \\ - 4x \times 3y = \\ \\ - 4 \times 3xy = \\ \\ - 12xy [/tex]
[tex]d) \frac{2}{3} {x}^{2} \times ( - \frac{9}{2}xy) = \\ \\ \frac{2}{3} {x}^{2} \times \frac{ - (9xy)}{2} = \\ \\ \frac{1}{3} {x}^{2} \times - 9xy = \\ \\ \frac{1 \times {x}^{2} \times - 9xy }{3} = \\ \\ \frac{ { - 9x}^{2}xy }{3} = \\ \\ \frac{ { - 9x}^{2 + 1}y }{3} = \\ \\ \frac{ { - 9x}^{3}y }{3} = \\ \\ - \frac{ {9x}^{3}y }{3} = \\ \\ { - 3x}^{3}y [/tex]
[tex]e) \sqrt{2} {x}^{3} \times ( { - \sqrt{8}x }^{2}) = \\ \\ \sqrt{2} {x}^{3} \times - 2 \sqrt{2} {x}^{2} = \\ \\ - 2 \sqrt{2 \times 2} {x}^{3} {x}^{2} = \\ \\ - 2 \sqrt{4} {x}^{3} {x}^{2} = \\ \\ - 2 \times {2x}^{3} {x}^{2} = \\ \\ - (2 \times 2) {x}^{3} {x}^{2} = \\ \\ - {4x}^{3} {x}^{2} = \\ \\ { - 4x}^{3 + 2} = \\ \\ { - 4x}^{5} [/tex]
[tex]f)( - 0,5 {x}^{2} {y}^{3}) \times ( + 4xy^{2}) = \\ \\ { - 0,5x}^{2} {y}^{3} \times {4xy}^{2} = \\ \\ ( - 0,5 \times 4) {x}^{2} {xy}^{3} {y}^{2} = \\ \\ { - 2x}^{2} {xy}^{3} {y}^{2} = \\ \\ { - 2x}^{2 + 1} {y}^{3 + 2} = \\ \\ { - 2x}^{3} {y}^{5} [/tex]
[tex]b)( { - 3a}^{2}) \times ( - 2a) = \\ \\ ( - 3 \times - 2) {a}^{2}a = \\ \\ {6a}^{2}a = \\ \\ {6a}^{2 + 1} = \\ \\ {6a}^{3} [/tex]